Involvement of male in birth preparedness in Tulsipur municipality of Dang district, Nepal - Bhusal, C K; Bhattarai, S (Journal of Chitwan Medical College, 2017)
Male in patriarchal societies of developing countries are identified as decision makers in all aspects of life. Every pregnant woman faces risk of life-threatening obstetric complications. A birth-preparedness package promotes active preparation and assists in decision-making for healthcare seeking in case of such complications. The present study attempted to assess the involvement of male in birth preparedness in Tulsipur Municipality of Dang District. A Descriptive Cross Sectional Study was conducted among 125 male including husbands of pregnant women and fathers of under one children in 2011, to assess the involvement of male in birth preparedness. Purposively record was reviewed from the Rapti Zonal Hospital as well as Municipality office, and respondent were identified using snowball sampling from community. More than half 52.8% of the respondents heard about Birth Preparedness. Nearly half 44.36% of the respondents plan for preparedness of birth, more than half 56.8% had thought to plan if emergency situation or complication arises during pregnancy and childbirth. Most 69.6% of the respondent has planned the place for giving birth to their child. Nearly half 51.8 % of respondent have plan for visiting their wives to Skill Birth Attendants. Only few 12.5% of the husbands had planned for transportation facility and identified Blood Donors if required’. About half 48% of the husbands are accompanying their wife for Antenatal Care. Most 88% of the husbands help their wives in household activities during pregnancy and childbirth. It shows that about half of the male were involved in Birth Preparedness.